PERBANDINGAN JENIS SAPI BRAHMAN CROSS STEER DAN BULL TERHADAP PRODUKSI KARKAS DAN HASIL IKUTAN - Yogi Saputra; Kurniawan Sinaga; Alfath Rusdhi (Bajang Institute, 2025)
The purpose of this study is to determine the differences between Brahman Cross Steer and Bull in terms of carcass production and by-products. The parameters of this study include slaughter weight, carcass weight, carcass weight percentage, fat weight, and fat percentage. The results of the study show differences in slaughter weight, carcass weight, fat, and their percentages between BX Bull and BX Steer cattle, with the best meat quality found in the BX Bull cattle.